Cape Verde : Third Review Under the Policy Support Instrument; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Cape Verde. (IMF Staff Country Reports; Country Report ;, 2008)
Cape Verde showed strong economic performance owing to its strong policies and macroeconomic stability under the Policy Support Instrument (PSI). Executive Directors appreciated the authorities' plan to consolidate macroeconomic stability, improve public sector financial management and tax administration, and strengthen regulation and supervision of the financial sector while reducing fiscal risks. They applauded the Bank of Cape Verde's (BCV) role in strengthening its framework for regulation and supervision. They stressed the need to strengthen the energy sector to enhance growth and poverty reduction. They welcomed the framework to combat money-laundering and financing of terrorism.